Taxation, social protection, and governance decentralization - Gil S. Epstein; Ira N. Gang (Rutgers University, Department of Economics, 2017)
Governments do not have perfect information regarding constituent priorities and needs. This lack of knowledge opens the door for groups to lobby in order to affect the government's taxation levels. We examine the political economy of decentralized revenue-raising authority in light of social protection expenditures by constructing a theoretical model of hierarchical contests and comparing the implications of centralized with decentralized governance. Increasing information available to the government may generate additional expenditures by interest groups trying to affect government taxation decisions. We show the potential existence of a poverty trap as a result of decentralization in taxation decisions.
Keywords: H77; D72; H73; 330; governance; decentralization; economic-models-of-political-processes; contests; rentseeking; intergovernmental-relations